2017
DOI: 10.1094/asbcj-2017-4043-01
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dilute Alkaline Steeping on Mold Contamination, Toxicity, and Nutritive Value of Maize Malt

Abstract: The primary aim of this research was to investigate the effect of dilute alkaline steeping on molds and toxicity of maize malt. Samples of maize were collected from one farm located in the Serbian autonomous region Vojvodina. Steeping regimes were performed by using 0.1, 0.2, and 0.3% NaOH solutions. The effects of these solutions on mold contamination, total aflatoxin (AFLA), deoxynivalenol (DON), zearalenone (ZON), rootlet length, moisture, total nitrogen, content of protein, fat content, ash content, conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…This decrease may occur due to the soaking process with dilute alkali and the leaching of inorganic compounds during the fermentation process. Jaukovic [40] reported that the ash content of maize malt reduced gradually during soaked in NaOH. However, the amount of ash content is considered high as the results are above the quality requirements of sorghum flour parameter, which is between 1.87 % and wheat flour ash content as a comparison.…”
Section: Proximate Analysis Of Fortified and Fermentation Flourmentioning
confidence: 99%
“…This decrease may occur due to the soaking process with dilute alkali and the leaching of inorganic compounds during the fermentation process. Jaukovic [40] reported that the ash content of maize malt reduced gradually during soaked in NaOH. However, the amount of ash content is considered high as the results are above the quality requirements of sorghum flour parameter, which is between 1.87 % and wheat flour ash content as a comparison.…”
Section: Proximate Analysis Of Fortified and Fermentation Flourmentioning
confidence: 99%